Health promotion of people in safety measures: perceptions of penitentiary agents and nursing (Research, Society and Development, 2022)
Objective: to understand how nurses and the penitentiary agents promote people's health of people in safety measures, from the perspective of the social determinants of health, at the Custody and Psychiatric Treatment Hospital. Method: exploratory and descriptive research with qualitative approach. Have participated in the study seven nursing professionals and eight prison guards, working in a hospital in Santa Catarina, Brazil. The semi-structured interviews were carried out between May and June 2019. The data was organized and analyzed by content analysis. Results: four categories have emerged: 1) Workers' conception of the concept of health; 2) Care of people as a safety measure; 3) Perceptions about the social determinants of health of people in security measures; 4) Health promoting actions in the hospital. Conclusion: is essential to develop an interdisciplinary work to address the social determinants of health of the people in security measures for the achievement of their rights.